Frequency of Presenting Complaints Among Women Having Adnexal Masses - Bibi, Lubna; Alam, Karishma; Sabeena, Abida; Bibi, Parveen; Irshad, Laila (Biological and Clinical Sciences Research Journal, 2025)
Adnexal masses in reproductive-age women present with a spectrum of gynecological and nonspecific symptoms that can delay diagnosis. Understanding the pattern of presenting complaints may facilitate earlier recognition and targeted evaluation. Data from local tertiary care centers in Pakistan remain limited. Objective: To determine the frequency of presenting complaints among women with adnexal masses at Hayatabad Medical Complex. Methodology: This study included 174 women aged 18 to 45 years with adnexal mass, which was confirmed on ultrasonography. Patients with recent surgery for pregnancy, chronic liver disease, or irritable bowel syndrome were excluded. The presenting complaints were dysmenorrhea which was defined as chronic spasmodic pelvic pain with menstruation, menorrhagia as prolonged bleeding over seven days or requiring pad changes more frequently than two-hourly and abdominal distension as a visibly swollen abdomen with bloating. Data analysis was performed using SPSS version 25. Results: Mean age of the cohort in this study was 29.87±8.52 years. The most frequently reported complaint was dysmenorrhea 60 (34.5%). Followed by menorrhagia, 41 (23.6%). Abdominal distension was observed in 20 (11.5%) cases. Younger age was associated with symptoms such as dysmenorrhea and menorrhagia. Conclusion: The findings of the present study indicate that dysmenorrhea is the most common presenting symptom in women with adnexal masses, followed by menorrhagia and abdominal distention.